Partial Unilateral Radial Hemimelia in Feline - Makino, Hérica; da Cruz, Thalita Priscila Peres Seabra; Bezerra, Kalinne Stephanie; Lima, Samara Rosolem; Travagin, David Ronald Parra; Nespoli, Pedro Brandini; Almeida, Arleana do Bom Parto Ferreira (Acta Scientiae Veterinariae, 2016)
Background: Hemimelia is a rare anomaly in which one of paired bone is congenital or partially absent. The etiology may be related to genetic and/or environmental factors. Clinically is observed the angulation of the affected limb, resulting in functional limitations as angular deformity, lameness and decreased range of motion. The diagnosis is based on clinical fndings and radiographic examination that detects the complete or partial absence of the affected bone and angular deviations. We aim to report a case of a partial unilateral radial hemimelia in a feline diagnosed at the Veterinary Hospital of the Federal University of Mato Grosso (HOVET-UFMT). Case: We attended at the HOVET-UFMT a two years old, feline, female, domestic short hair, presenting as a complaint the presence of a friable mass in the oral cavity for a year and a deformity in the left forelimb since birth, showing swallowing diffculties, lameness and diffculty support. On clinical examination, we obeserved the left forelimb ﬂexed and deviation in the medial direction, shortening of the limb, no crepitation during handling and evident lameness. Radiographic examination in the craniocaudal and mediolateral projections of the thoracic limbs revealed the partial absence of the radius with just a trace of the proximal radial epiphysis, shortening and a marked ulnar curvature, producing a signifcant deviation of the limb in the cranial direction. To perform incisional biopsy of the mass in the oral cavity, the patient underwent general anesthesia, but died after the procedure. The animal was sent to the Veterinary Pathology department to perform the necropsy that confrmed the diagnosis of Gingivitis-Stomatitis-Pharyngitis Complex, evidencing a hyperplasia of the gingival epithelium and tongue, diffuse and severe lymphoplasmacytic inﬂammation of the lamina propria, multifocal hydropic degeneration of the basal layer with presence of necrotic acanthocytes and even multiple areas of ulceration. After routine necropsy, the dissection of the left forelimb was carried out in order to be observed macroscopically the anomaly and its presentation, confrming the radiographic fndings. Discussion: In this case, we could not determine the origin of the hemimelia because both environmental and genetic factors can inﬂuence the embryonic development of the limb, particularly in the period between the 16th and the 28th day after fertilization. The radial hemimelia is a serious congenital pathology and when presented bilaterally is often associated with other malformations. In this case, the malformation was presented in a partial way (the absence of a segment) only in the left forelimb. Macroscopically there were not any other abnormalities. The conservative treatment was instituted with the maintenance of the animal in smooth and soft surface to avoid the occurrence of ulcerations on the contact areas with the ground. It is concluded that the history and physical examination associated with radiological fndings were able to establish the defnitive diagnosis of the partial unilateral hemimelia of the left radius. Keywords: anomaly, absence, cat, limb.